Developing Community-Based Understandings of Food Security, Food Sovereignty and Indigenous Food Self-Determination in Collaboration with Three First Nations in Northern, Ontario - Cherry, Dakota (University of Guelph, 2024)
This research study explores understandings and experiences of food insecurity among Indigenous Peoples in Canada, focusing on three First Nations in Northern Ontario. It critiques existing measurement tools for failing to capture Indigenous experiences and argues for policies informed by community-specific and culturally contextual understandings of food sovereignty and security. The research defines Indigenous food self-determination, emphasizing the importance of integrating local and scientific knowledge into governance and policy approaches. The study highlights the strong link between food sovereignty as a necessary pathway towards food security, noting challenges such as food accessibility, affordability, and quality. Child food insecurity rates were particularly concerning, with issues like limited meal ingredients and hunger. Results show that community members see their collective as the primary safety net against food insecurity, underscoring the importance of community-driven solutions. The findings suggest that braiding Indigenous and Western knowledge is key to developing effective, culturally relevant policies. Ontario Agri-Food Innovation Alliance